Implementation of soft switching in resonant converters - Mehedy, Mehedy Hachan; Zoardar, Md. Akib Hasan; Islam, Sayed Alvee; Ahmed, Shakil (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.